HAND HYGIENE COMPLIANCE AMONG NURSES WORKING IN CRITICAL CARE UNITS AT CHITWAN MEDICAL COLLEGE, CHITWAN, NEPAL - Uprety, Sunita; Devi Kandel, Tika; Rajbanshi, Laxmi (Journal of Chitwan Medical College, 2024)
Background: Hospital Acquired Infections (HAIs) is an important cause of morbidity and mortality in intensive care units. Hands of healthcare personnel are the major source of cross transmission of pathogens in healthcare facilities. Hand hygiene is one of the most efficacious method for infection control program in health care settings. Thus, the purpose of this study was to assess the hand hygiene compliance among nurses working in critical care units. Methods: This descriptive cross-sectional study involved 106 nurses from 6 critical care units of Chitwan Medical College. Sample was selected by using consecutive sampling technique. Data was collected from 15th November 2022 to 12th January 2023 by using WHO hand hygiene observation form. Data were analyzed by using descriptive statistics. Results: The overall hand hygiene compliance rate was 44.84%. Based on WHO ‘5 moments of hand hygiene’, maximum compliance was seen for the moment i.e. after touching patient (53.63%) whereas minimum in moment i.e. before aseptic and clean procedure (18.51%). The highest compliance rate was found in NICU (58.60%) followed by PICU (48.97%) and MICU I (48.68%). Conclusions: Overall, the hand hygiene compliance was below average among the nurses. Thus, continuous training, periodic assessment of the nurses’ knowledge, performance feedback and conducting continuous research activity in order to fill any gaps and identify the barriers to hand hygiene adherence would be advisable.